MAITabolism2 – the emerging understanding of MAIT cell metabolism and their role in metabolic disease - Kedia-Mehta, Nidhi; Hogan, Andrew E. (Frontiers in Immunology, 2023)
Mucosal associated invariant T (MAIT) cells are a population of unconventional innate T cells due to their non-MHC restriction and rapid effector responses. MAIT cells can recognise bacterial derived antigens presented on the MHC-like protein via their semi-restricted T cell receptor (TCR). Upon TCR triggering MAIT cells rapidly produce a range of effector molecules including cytokines, lytic granules and chemokines. This rapid and robust effector response makes MAIT cells critical in host responses against many bacterial pathogens. MAIT cells can also respond independent of their TCR via innate cytokines such as interleukin (IL)-18, triggering cytokine production, and are important in anti-viral responses. In addition to their protective role, MAIT cells have been implicated in numerous inflammatory diseases, including metabolic diseases often contributing to the pathogenesis via their robust cytokine production. Effector cells such as MAIT cells require significant amounts of energy to support their potent responses, and the type of nutrients available can dictate the functionality of the cell. Although data on MAIT cell metabolism is just emerging, several recent studies are starting to define the intrinsic metabolic requirements and regulators of MAIT cells. In this review we will outline our current understanding of MAIT cell metabolism, and outline their role in metabolic disease, and how disease-related changes in extrinsic metabolism can alter MAIT cell responses.